(untitled) (Amsterdam, 2003)
Hardbound. Climate change is an issue that is highly debated around the globe. This book brings together the papers that were presented at a conference dedicated to this issue, held in Kyoto in October 2002. Covering a broad range of areas, the topics presented will benefit both those working in the field of carbon dioxide recovery and sequestration, and those looking at the effects of non carbon dioxide greenhouse gases. An overview of the Research and Design technologies which aid in mitigating climate change is included, which will be invaluable to those researching new opportunities for dealing with this problem.
Keywords: Greenhouse gases,Air; Environmental aspects,Congresses,Purification,Technological innovations,Congresses